An Iconographical Study and Iconological Interpretation of the Jewellery of Three Ancient Egyptian Royal Women of the 12th Dynasty - Schäder, Jo-Marí (University of Pretoria, 2022)
Mini Dissertation (MA (Ancient Languages))--University of Pretoria, 2021.